2012
DOI: 10.1021/cb200542j
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Genetic Code of Caenorhabditis elegans Using Bacterial Aminoacyl-tRNA Synthetase/tRNA Pairs

Abstract: The genetic code specifies 20 common amino acids and is largely preserved in both single and multicellular organisms. Unnatural amino acids (Uaas) have been genetically incorporated into proteins by using engineered orthogonal tRNA/aminoacyltRNA synthetase (RS) pairs, enabling new research capabilities and precision inaccessible with common amino acids. We show here that Escherichia coli tyrosyl and leucyl amber suppressor tRNA/RS pairs can be evolved to incorporate different Uaas in response to the amber stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 44 publications
0
98
0
Order By: Relevance
“…Yet, limitations of the technology remain: most importantly these include the need for more widespread access to the required plasmids and the global applicability towards all protein systems. However, recent impressive advances in the field such as amber suppression in living animals 197,198 , and significant increases in suppression efficiency by knockout of the gene for RF1 in E. coli 199 are beginning to open up the possibility of amber-stop codon suppression becoming an indispensable tool for the incorporation of unnatural 'tags' into proteins to undertake site-selective modification. The creation of an 'amber-free' E. coli variant is also farsighted in this regard 200 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…Yet, limitations of the technology remain: most importantly these include the need for more widespread access to the required plasmids and the global applicability towards all protein systems. However, recent impressive advances in the field such as amber suppression in living animals 197,198 , and significant increases in suppression efficiency by knockout of the gene for RF1 in E. coli 199 are beginning to open up the possibility of amber-stop codon suppression becoming an indispensable tool for the incorporation of unnatural 'tags' into proteins to undertake site-selective modification. The creation of an 'amber-free' E. coli variant is also farsighted in this regard 200 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…24, 42, 43 These latter pairs are especially advantageous as they allow aaRSs to be evolved in E. coli prior to transfer of the machinery to more diverse eukaryotic hosts. Utilizing these orthogonal pairs, ncAAs have been encoded in B. cereus, 89 P. pastoris, 90 C. elegans, 91, 92 D. melanogaster, 93 A. thaliana, 94 Zebrafish embryos, 95 and the mouse. 9699 More recently, it has been demonstrated that a native Trp aaRS/tRNA pair in E. coli can be functionally replaced with a counterpart from yeast, and the liberated Trp pair can be used to encode ncAAs in bacteria.…”
Section: Expanding the Genetic Codementioning
confidence: 99%
“…We showed that this method can be used to express different tRNAs in mammalian cells, including tRNACUATyr and tRNACUAleu from E. coli 18 and tRNACUApyl from Methanosarcina . 22 In addition, we applied this approach successfully in various cells and animals, including mammalian cell lines, 18 primary neurons, 18 stem cells, 19 C. elegans , 23 mouse, 24,25 and zebrafish. 25 Others have later applied this approach in plant 26 and fruit fly.…”
Section: Introductionmentioning
confidence: 99%
“…18 In combination with the efficient tRNA expression discussed above, the transfer strategy has enabled various Uaas to be genetically encoded in mammalian cells, 18 primary neurons, 18 stem cells, 19 and animals. 23-25 …”
Section: Introductionmentioning
confidence: 99%